Unlocking Employee Performance Through Digital Human Resource Management: The Mediating Role of Employee Engagement - Mira Labi Bandhaso; Carolus Askikarno Pala’langan Pala’langan (Penerbit Goodwood, 2026)
Purpose: This study aims to investigate the effect of Digital Human Resource Management (DHRM) on employee performance, with employee engagement serving as a mediating mechanism, within organizations operating in an emerging economy context. Research Methodology: A quantitative research design was applied using a cross-sectional survey of employees working in organizations that have implemented digital HR practices in Makassar, Indonesia. Data were collected through a structured questionnaire and analyzed using PLS-SEM to examine both direct and indirect relationships among the study variables. Results: The findings reveal that DHRM has a positive and significant effect on employee performance and employee engagement. Employee engagement also demonstrates a positive and significant effect on employee performance and partially mediates the relationship between DHRM and performance. These results indicate that digital HR practices enhance performance not only through improvements in operational efficiency but also by strengthening employees’ psychological engagement with their work. Conclusions: The study concludes that DHRM functions as a critical organizational resource that supports employee engagement and performance. Digital HR transformation is more effective when it is implemented in ways that promote employees’ motivational and psychological investment in their work roles. Limitations: This study is limited by its cross-sectional design, reliance on self-reported measures, and focus on a single regional context, which may limit causal inference and generalizability. Contributions: This research contributes to the Digital HRM literature by offering a mechanism-based explanation of the DHRM–performance relationship through employee engagement and by providing empirical evidence from a secondary metropolitan area in an emerging economy.